Continuously tunable substrate integrated waveguide bandpass filter in liquid crystal technology with magnetic biasing. Issue 20 (1st October 2015) - Prasetiadi, A.E.; Karabey, O.H.; Weickhmann, C.; Franke, T.; Hu, W.; Jost, M.; Nickel, M.; Jakoby, R.
Abstract : A liquid crystal filled continuously tunable substrate integrated waveguide filter is proposed which has a high‐quality ( Q ) factor. To measure the Q ‐factor, a single resonator measurement is performed by using magnetic biasing in a lab demonstrator for a proof of concept. The unloaded Q ‐factor is 102–105.6. The resonator is employed to create a three‐pole Chebyshev filter with a centre frequency of 22 GHz and a bandwidth of 600 MHz. Measurement results show a 6 dB insertion loss with a return loss of about 10 dB. The filter is continuously tunable within a tuning range of 610 MHz.